Neurologic functional outcomes of decompressive hemicraniectomy versus conventional treatment for malignant middle cerebral artery infarction: a systematic review and meta-analysis - Li, Yuping; Lu, Guangyu (World neurosurgery, 2017)
Objective - The aims of this study were to evaluate decompressive hemicraniectomy (DHC) versus conventional treatment (CT) for patients with malignant middle cerebral artery (MCA) infarction and to investigate the impact of age and surgical timing on neurologic function and mortality. - Methods - We searched English and Chinese databases for randomized controlled trials or observational studies published before August 2016. Outcomes included good functional outcome (GFO), mortality, and National Institutes of Health Stroke Scale and Barthel index scores. - Results - This meta-analysis included 25 studies (1727 patients). There were statistically significant differences between DHC and CT groups in terms of GFO (P < 0.0001), mortality (P < 0.00001), and National Institutes of Health Stroke Scale and Barthel index scores (P < 0.0001) at different follow-up points. Significant differences were observed between the groups in survival with moderately severe disability (P < 0.00001); no differences were observed in survival with severe disability. In the subgroup analysis, in the DHC group, GFO was less in patients >60 years old (9.65%) versus ≤60 years old (38.94%); more patients >60 years old had moderately severe or severe disability (55.27%) compared with patients ≤60 years old (44.21%). - Conclusions - DHC could significantly improve GFO and reduces mortality of patients of all ages with malignant MCA infarction compared with CT, without increasing the number of patients surviving with severe disability. However, patients in the DHC group more frequently had moderately severe disability. Patients >60 years old with malignant MCA infarction had a higher risk of surviving with moderately severe or severe disability and less GFO.
Available online 24 December 2016
Gesehen am 18.09.2018